6‐shogaol induces apoptosis and enhances radiosensitivity in head and neck squamous cell carcinoma cell lines. (23rd November 2017) - Kotowski, Ulana; Kadletz, Lorenz; Schneider, Sven; Foki, Elisabeth; Schmid, Rainer; Seemann, Rudolf; Thurnher, Dietmar; Heiduschka, Gregor
Abstract : Ginger ( Zingiber officinale Roscoe) is used for a wide array of conditions in traditional medicine in Asia, but little is known about the effect on head and neck cancer. In this study, the effect of two major pharmacologically active compounds of ginger, 6‐gingerol and 6‐shogaol, were studied on head and neck cancer cell lines. Furthermore, experiments in combination with established treatment methods for head and neck cancer were performed. Proliferation assays showed a dose‐dependent reduction of cell viability. Flow cytometry analysis revealed the induction of apoptosis. Western blot analysis indicated that the antiapoptotic protein survivin was suppressed after treatment. Although a combination of 6‐shogaol with cisplatin exhibited no synergistic effect, the combination with irradiation showed a synergistic reduction of clonogenic survival. In conclusion, ginger compounds have many noteworthy effects on head and neck cancer cell lines. In particular, the enhancement of radiosensitivity is remarkable.